Women waging law in Elizabethan England - Stretton, Tim, 1963- (Cambridge studies in early modern British history., 1998)
This book investigates the surprisingly large number of women who participated in the vast expansion of litigation in sixteenth- and seventeenth-century England. Making use of legal sources, literary texts, and the neglected records of the Court of Requests, it describes women's rights under different jurisdictions, considers attitudes to women going to court, and reveals how female litigants used the law, as well as fell victim to it. In the central courts of Westminster, maidservants sued their masters, widows sued their creditors, and in defiance of a barrage of theoretical prohibitions, wives sued their husbands. The law was undoubtedly discriminatory, but certain women pursued actively such rights as they possessed. Some appeared as angry plaintiffs, while others played upon their poverty and vulnerability. A special feature of this study is the attention it pays to the different language and tactics that distinguish women's pleadings from men's pleadings within a national equity court.